2022
DOI: 10.1093/ndt/gfac003
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming barriers in the design and implementation of clinical trials for acute kidney injury: a report from the 2020 Kidney Disease Clinical Trialists meeting

Abstract: Acute Kidney Injury (AKI) is a growing epidemic and is independently associated with increased risk of death, chronic kidney disease, and cardiovascular events. Randomized-controlled trials (RCTs) in this domain are notoriously challenging, and many clinical studies in AKI have yielded inconclusive findings. Underlying this conundrum is the inherent heterogeneity of AKI in its etiology, presentation, and course. AKI is best understood as a syndrome, and identification of AKI subphenotypes is needed to elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…We speculate that uncharacterized clinically and physiologically distinct substages exist within critically ill children with AKI and that they are associated with differences in the risk of adverse outcomes. Moreover, because of the inherent heterogeneity of AKI in its etiology and pathophysiology, human studies investigating the prevention and treatment of AKI remain largely inconclusive [ 43 , 44 ]. The identification of AKI subphenotypes linked to underlying pathophysiologic processes may parse the heterogeneity in the AKI phenotype and identify treatment-responsive AKI subtypes [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that uncharacterized clinically and physiologically distinct substages exist within critically ill children with AKI and that they are associated with differences in the risk of adverse outcomes. Moreover, because of the inherent heterogeneity of AKI in its etiology and pathophysiology, human studies investigating the prevention and treatment of AKI remain largely inconclusive [ 43 , 44 ]. The identification of AKI subphenotypes linked to underlying pathophysiologic processes may parse the heterogeneity in the AKI phenotype and identify treatment-responsive AKI subtypes [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, human recombinant alkaline phosphatase is an endogenous detoxification enzyme with anti-inflammatory effects. In a phase II trial of patients with sepsis-related AKI, it significantly improved long-term renal function and reduced mortality ( Lazzareschi et al, 2022 ). Moreover, Sirtuin 1 (SIRT1) can inhibit the expression of inflammatory genes and reduce inflammatory tissue injury ( Fan et al, 2013 ).…”
Section: The Treatment Of Oxidative Stress Regulation For Akimentioning
confidence: 99%
“…Randomized controlled trials reported in the literature are often affected by poor generalizability, and pragmatic trials have become an increasingly utilized workaround approach to overcome logistical limitations and explore routine interventions demonstrating equipoise in clinical practice 1 . Intravenous albumin, for example, is commonly administered in the perioperative setting despite lacking supportive evidence.…”
Section: Introductionmentioning
confidence: 99%